Contribuições teórico-metodológicas da educação em direitos humanos ao Programa Educacional de Resistência às Drogas e à Violência – PROERD do estado do Rio Grande do Norte - Lira Júnior, Guinaldo da Costa (2020)
Social violence, present in our daily lives, has the most varied origins, among them the consumption of drugs, making it clear that repressive strategies did not have the intended effects. The Educational Program on Resistance to Drugs and Violence - PROERD presents itself as an educational and preventive alternative to the use of drugs and violence. In this dissertation, we propose to answer the following problem: Could the transversality of Education in Human Rights offer theoretical and methodological contributions to PROERD from the perspective of building a culture of human rights? For this, we established as a general objective, to analyze PROERD, through its Curriculum for children of the 5th year of elementary school, under the perspective of a public policy of confrontation and prevention of drugs seeking to investigate possible clues of the transversality of Education in Rights Humans that assist in the construction of a culture of human rights, and as specific objectives, we have: a) Conceptualize PROERD within the field of public policies to confront and prevent drugs in Brazil, investigating the role of Instructor PROERD as a social educator; b) Delimit the field of public policies on Education in Human Rights, discussing its historicity, plans, guidelines, concepts and principles; c) Analyze the PROERD Curriculum for the 5th year of elementary school seeking to investigate and identify in it clues of the transversality of Education in Human Rights, thus establishing its correlation with Human Rights, which allow it to contribute to the construction of a culture of rights humans. The methodology is configured as a research with basic-strategic purpose, qualitative approach and descriptive-explanatory objective, which uses the inductive method, with procedures for the collection of bibliographic and documentary data and content analysis (Bardin, 1977), from the perspective of critical pedagogy. As a result, we obtained the conceptualization of PROERD in the field of public policies to confront and prevent drugs in Brazil, the delimitation of the epistemic field of public policies on Education in Human Rights and the identification of clues of the transversality of Education in Human Rights in the analyzed curriculum. In conclusion, we can state that PROERD is a public policy on drugs, of an educational and preventive nature, which dialogues with the contents of Human Rights through the transversality of Education in Human Rights, thus helping to build a culture of Human Rights.